Ecotoxicological assessment of sanitary sewer overflows and rainfall dynamics offers insights into conditions for potential adverse ecological outcomes - Anu Kumar; Graeme E. Batley; Merrin Adams; Thao V. Nguyen; Bhanu Nidumolu; Huong Nguyen; Adrienne Gregg; Michele Cassidy; Colin H. Besley (Science of The Total Environment, 2024)

Site-specific risk-based threshold (RBT) concentrations for sewage-associated markers in estuarine swimming waters - Warish Ahmed; Mary E. Schoen; Jeffrey Soller; Joanna Ciol Harrison; Kerry A. Hamilton; Metasebia Gebrwold; Stuart L. Simpson; Sudhi Payyappat; Michele Cassidy; Nathan Harrison; Colin Besley (Science of The Total Environment, 2024)

Assessing the nucleic acid decay of human wastewater markers and enteric viruses in estuarine waters in Sydney, Australia - Warish Ahmed; Asja Korajkic; Metasebia Gabrewold; Sudhi Payyappat; Michele Cassidy; Nathan Harrison; Colin Besley (Science of The Total Environment, 2024)

Comparing the decay of human wastewater-associated markers and enteric viruses in laboratory microcosms simulating estuarine waters in a temperate climatic zone using qPCR/RT-qPCR assays - Warish Ahmed; Asja Korajkic; Wendy J. Smith; Sudhi Payyappat; Michele Cassidy; Nathan Harrison; Colin Besley (Science of The Total Environment, 2024)

Reduction of human fecal markers and enteric viruses in Sydney estuarine waters receiving wet weather overflows - Warish Ahmed; Sudhi Payyappat; Michele Cassidy; Nathan Harrison; Colin Besley (Science of The Total Environment, 2023)

Tracking contaminants of concern in wet-weather sanitary sewer overflows - Colin H. Besley; Graeme E. Batley; Michele Cassidy (Environmental Science and Pollution Research, 2023)
Four representative sites in the greater city of Sydney, Australia, were selected for a study of the wet-weather overflow of sanitary (separate to stormwater) sewerage systems. Water samples were collected by autosamplers from up to eight wet weather overflow events over 16 months and from companion receiving water sites. The objective was to identify the risks posed by sewage contaminants to aquatic biota in the receiving waters, to aid in prioritising management actions. Twelve organic contaminants were identified in influents across the four sites under rainfall ingress diluted conditions, with measurements showing that the highest concentrations were restricted to the anti-inflammatory acetaminophen and the diabetes medication metformin. Lesser contaminants included theobromine, ibuprofen, sucralose, and three benzotriazoles (mainly 1-H benzotriazole). An assessment of the toxicity of the identified organic chemicals indicated that none appeared to pose concerns for ecosystem health before wet-weather ingress dilution, and this was even less likely after dilution in the receiving waters. Metal concentrations were low; however, ammonia concentrations in the influent did pose a risk to ecosystem health, although receiving water dilution diminished this risk at four of the five receiving water locations studied.

Microbial source tracking of untreated human wastewater and animal scats in urbanized estuarine waters - Warish Ahmed; Sudhi Payyappat; Michele Cassidy; Nathan Harrison; Colin Besley (Science of The Total Environment, 2023)